MYC and KRAS cooperation: from historical challenges to therapeutic opportunities in cancer - Casacuberta-Serra, Sílvia; González-Larreategui, Íñigo; Capitán-Leo, Daniel; Soucek, Laura (Signal transduction and targeted therapy, 2024)
RAS and MYC rank amongst the most commonly altered oncogenes in cancer, with RAS being the most frequently mutated and MYC the most amplified. The cooperative interplay between RAS and MYC constitutes a complex and multifaceted phenomenon, profoundly influencing tumor development. Together and individually, these two oncogenes regulate most, if not all, hallmarks of cancer, including cell death escape, replicative immortality, tumor-associated angiogenesis, cell invasion and metastasis, metabolic adaptation, and immune evasion. Due to their frequent alteration and role in tumorigenesis, MYC and RAS emerge as highly appealing targets in cancer therapy. However, due to their complex nature, both oncogenes have been long considered “undruggable” and, until recently, no drugs directly targeting them had reached the clinic. This review aims to shed light on their complex partnership, with special attention to their active collaboration in fostering an immunosuppressive milieu and driving immunotherapeutic resistance in cancer. Within this review, we also present an update on the different inhibitors targeting RAS and MYC currently undergoing clinical trials, along with their clinical outcomes and the different combination strategies being explored to overcome drug resistance. This recent clinical development suggests a paradigm shift in the long-standing belief of RAS and MYC “undruggability”, hinting at a new era in their therapeutic targeting.